Asymmetric spatial light modulator in a package - GRASSER REGIS; HUIBERS ANDREW (2006)
Disclosed herein is a micromirror package having a micromirror being attached to a supporting surface of a package substrate, and sealed between the package substrate and a package cover, whereas the micromirror array is placed offset the center of the supporting surface.